Combined methods of mutation breeding and genetice modifications enhanced rhamnolipids production of oil well Indigenous Pseusdomonas aeruginosa - Mingxin Liu; Jin Sun; Xin Song (Scientific Reports)
Abstract Rhamnolipids (RLs) are considered as the most popular and efficient biosurfactant, which exhibit superior thermal stability, chemical resistance, low ecotoxicity, biodegradability and good antimicrobial activity. The RLs-producing wild-type strains cannot produce high-yield rhamnolipids to meet with the demand of industrial applications. In view of the problems existing in the practical application of RLs, atmospheric and room temperature plasma-mediated (ARTP) mutagenesis, ultraviolet mutagenesis, ethyl methane sulfonate (EMS) were used alone and combined to mutate and screen Pseudomonas aeruginosa SH6 for many rounds, and a mutant strain P. aeruginosa EZD3 that produced 5.05 g/L of RLs was obtained. Then the original promoter of the rhamnosyl transferase genes was replaced with a strong promoter in strain EZD3, a recombinant strain P. aeruginosa APA1 produced 7.32 g/L of RLs, which showed a 4.67 times increase in RLs production than the original strain P. aeruginosa SH6. Finally, after the optimization of the carbon source of for RLs production, the RLs yield of the recombinant strain P. aeruginosa APA1 reached 7.59 g/L.